Reorganizing a countywide school district: A critical analysis of politics and policy development toward decentralization - Diem, Sarah; Sampson, Carrie; Browning, Laura Gavornik (Education Policy Analysis Archives, 2018)
Policymakers and educational leaders continue to use school district decentralization as a reform effort that attempts to shift power and authority from central office administration to school-level leadership. In 2015, the Nevada Legislature passed legislation to restructure the Clark County School District (CCSD), the state’s largest school district, with the intent of breaking it up into smaller districts but instead evolving to decentralization. In this article, we use case study methods to explore the events leading up to the reorganization of CCSD. We take a critical perspective on Kingdon’s multiple streams framework to analyze the reorganization efforts, focusing specifically on how Nevada’s political context provided a window of opportunity for the reorganization to occur. We also examine the extent to which equitable educational opportunity was a factor in these efforts. Our analysis of the reorganization of CCSD contributes to a wider understanding of state-level policy development and politics within contemporary educational contexts. In this case, we find that state-level policymakers successfully leveraged the opportunity to enact the power and authority necessary to significantly and rapidly impact the structure of one of the largest school districts in the United States.